2016
DOI: 10.1097/cej.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Overweight, obesity, and breast cancer screening

Abstract: Obesity is associated with poor breast cancer (BC) prognosis. Larger tumor size and more advanced disease stage at diagnosis could partly explain this outcome and nonadherence of obese women to BC screening may play a role. We examined the relationship between BMI (kg/m) and the use of mammography in Switzerland as well as separately in the German-speaking part with mainly opportunistic screening and in the French-speaking part with organized programs. We analyzed the data of 50-69-year-old women (n=3121) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…In addition, before hospitalization, patients with and without obesity were equally nonadherent to BRC/CRC outpatient screening. This finding was consistent for BRC/CRC screening in larger studies, noting no differences in adherence between women with and without obesity [35][36][37] ; however, past studies have found morbidly obese Whites, low household income, and tobacco use to be risk factors for nonadherence to mammograms. 5,14,15,31 Furthermore, Denberg and colleagues found that lack of scheduled appointments, female sex, and type of insurance predicted nonadherence to screening colonoscopies.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, before hospitalization, patients with and without obesity were equally nonadherent to BRC/CRC outpatient screening. This finding was consistent for BRC/CRC screening in larger studies, noting no differences in adherence between women with and without obesity [35][36][37] ; however, past studies have found morbidly obese Whites, low household income, and tobacco use to be risk factors for nonadherence to mammograms. 5,14,15,31 Furthermore, Denberg and colleagues found that lack of scheduled appointments, female sex, and type of insurance predicted nonadherence to screening colonoscopies.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, there is another hypothesis that obesity females do less breast screening, and they are more difficult to find small lumps due to too much fatty in breast, so obesity patients tend to have more advanced disease at initial diagnosis [26, 36]. However, a study by Eichholzer et al reported no differences in mammography screening attendance between normal weight and obese and underweight women [38].…”
Section: Discussionmentioning
confidence: 99%
“…Another important consideration is that our results based on women regularly attending screening suggest that it is especially important for women with high BMI to attend screening. There is mixed evidence from prior studies on the current attendance rate; in some studies women with high BMI were less likely to attend than women with normal BMI while in others there was no significant difference [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%